Desenvolvimento de phantoms para tomografia com feixe de prótons - Milhoretto, Edney (2012)
In this work phantoms were developed for two tomographic systems with proton beam (pCT). A phantom was developed for a mini scanner using a low energy proton beam, which is being developed at the Federal University of Technology - Parana (UTFPR) and tested at the CV-28 cyclotron at the Institute of Nuclear Engineering (IEN). Two additional phantoms were developed for the pCT prototype at Loma Linda University Medical Center – CA, USA (LLUMC). SRIM and Geant4 codes were used to simulate all the elements of the prototypes. Improvements were made in the UTFPR/IEN prototype such as electronic control system of mechanism, controlled by a computer program, upgrade in the collimation system to improve the resolution of reconstructed images obtained by simulations. Experimental energy loss tests were done with polyethylene protons of high density (PEAD) in CV-28. Experiments of energy loss in layers of polystyrene at the LLUMC were also done and compared with simulated data. Both phantoms were constructed and tested in the prototype of LLUMC and a program was developed for data analysis.